Handbook of palladium-catalyzed organic reactions : synthetic aspects and catalytic cycles - Malleron, Jean-Luc (Academic Press, 1997)
This handbook provides a synoptic description of the main types of reactions which are catalyzed by Palladium and the mechanism which causes the reactions. Each reaction is presented in graphical form and classified according to the type of transformation involved.